Perbandingan Konten Instagram Disbudporaparsby dan Roeang.Jenama Pada Gelaran Piala Dunia U-17 2023 - Bagas Dwiya Yudhana; Restu Ismoyo Aji (Journal of Creative Student Research, 2023)
Motion graphic is one of the graphic design techniques that uses animation to convey information visually. Motion graphic can make visual presentation content richer and clearer in delivering messages. Motion graphic can also help content attract audiences. This study aims to compare the effectiveness of visual presentation on static content and content with motion graphic about the U-17 World Cup 2023. The study was conducted with a qualitative descriptive method. Data collection methods involved interviews to find out the responses of the informants to the content that used motion graphic and static content, as well as observations through direct observation to obtain the informants’ responses, enthusiasm, and understanding of the messages conveyed in both types of content. The results of the study showed that the use of motion graphic can improve the respondents’ understanding and enthusiasm for the message in the content of major sporting events such as the U-17 World Cup. In addition, the use of motion graphic can be a consideration for content creators who use motion graphic. This study has the potential to improve the effectiveness of the message delivered through motion graphic that is educational and informative.